1993
DOI: 10.1002/hep.1840170221
|View full text |Cite
|
Sign up to set email alerts
|

Confocal microscopy immunofluorescence localization of desmin and other intermediate filament proteins in fetal rat livers

Abstract: Immunolocalization of desmin in fetal rat livers shows that on day 12 of gestation a high number of liver cells express desmin. This number decreases from day 14 onward. On day 20 about the same density of desmin-containing cells is found in fetal rat livers as is found in adult rat livers. Desmin-containing cells show two types of labeling patterns, especially on days 12 and 13 of gestation: (a) a basketlike network of intermediate filaments throughout the whole cell, similar to the labeling pattern of cytoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 39 publications
2
8
1
Order By: Relevance
“…Currently, the bulk of evidence supports their originating from either endoderm (300,624,666) or the septum transversum (553) as it forms from cardiac mesenchyme during invagination of the hepatic bud (135,728,733). In support of a septum transversum origin, stellate cells express the mesoderm transcriptional factor Foxf1, which is typically localized to the septum transversum mesenchyme during liver development (280).…”
Section: A Embryologic Origin(s)mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the bulk of evidence supports their originating from either endoderm (300,624,666) or the septum transversum (553) as it forms from cardiac mesenchyme during invagination of the hepatic bud (135,728,733). In support of a septum transversum origin, stellate cells express the mesoderm transcriptional factor Foxf1, which is typically localized to the septum transversum mesenchyme during liver development (280).…”
Section: A Embryologic Origin(s)mentioning
confidence: 99%
“…In support of a septum transversum origin, stellate cells express the mesoderm transcriptional factor Foxf1, which is typically localized to the septum transversum mesenchyme during liver development (280). In support of an endoderm origin, on the other hand, it has been suggested that stellate cells and hepatoblasts share a common origin based on the transient coexpression of cytokeratins in both cell types (300,666).…”
Section: A Embryologic Origin(s)mentioning
confidence: 99%
“…Recent studies reported that, in young fetal rat livers, almost all nonhaematopoietic liver cells, including hepatoblasts, transiently coexpressed desmin and cytokeratins, which were used as markers for hepatic stellate cells and hepatoblasts, respectively (Vassy et al 1993 ;Kiassov et al 1995). To verify whether this phenomenon could be observed in the fetal mouse liver, we studied the immunolocalisation of desmin with E-cadherin and cytokeratins at various stages of mouse liver development.…”
Section: mentioning
confidence: 99%
“…Recently, some groups reported that at early stages of rat liver development, most nonhaematopoietic cells, including hepatoblasts, had transient coexpression of desmin and epithelial cell-specific cytokeratins in liver (Vassy et al 1993 ;Kiassov et al 1995). Based on these results, they proposed the idea that nonhaematopoietic desmin-positive cells give rise to both hepatocytes and hepatic stellate cells.…”
mentioning
confidence: 99%
“…The embryologic origin of HSCs remains unresolved. Based on expression markers, potential origins of HSCs include endoderm (cytokeratins) [6], or the septum transversum mesenchyme (Foxf1, vimentin) [7], or neural crest (GFAP, synaptophysin, N-CAM) [8] and P75 [9]). However, the neural crest origin has been challenged [10].…”
Section: Introductionmentioning
confidence: 99%